MANAGEMENT OF THE COUNTRY BORDER THROUGH THE EXPORT DEVELOPMENT OF AGRICULTURAL COMMODITIES IN THE INDONESIAN BORDER - Pandu Adi Cakranegara; Zet Ena; Miftahorrozi Miftahorrozi; Eko Sutrisno; Alya Elita Sjioen (Jurnal Ekonomi, 2022)
The management of border areas in Indonesia has faced strategic issues, namely the issue of managing state boundaries and the problem of managing border areas. The purpose of this study is to organize the management of national borders through the development of Agribusiness commodity exports in the Indonesia-Malaysia PLBN on the growth of the economic sector. This research method is qualitative with the type of case study research. The location of this research is Aruk Sambas, Indonesia-Malaysia. Primary data sources are experts and the development of state border areas in Sambas Regency. Data analysis proceeds as follows: First, the researcher rereads the data as a whole to provide an understanding of the overall narrative generated by the interviews. The results of this study indicate that there is a need for collaborative border management based on institutions and the international community for cooperation in achieving goals.